Practical considerations and applications of postactivation performance enhancement in group training: delayed performance enhancing triplexes - Lepkowski, M.; Leiting, K. A.; Koch, A. J. (Strength and Conditioning Journal, 2021)
Athletes may increase power output through eliciting postactivation performance enhancement (PAPE). Muscle force and power may be increased during PAPE by coupling of 2 exercises, termed a "strength-power potentiating complex" (SPPC). Implementing SPPCs in the field is complicated by the need to use rest periods of several minutes in duration, which is impractical when training large numbers of athletes simultaneously within a short time. We propose delayed performance enhancing triplexes as a solution: which involve inserting an accessory exercise in between a heavy resistance exercise and a plyometric movement, which allows for training to continue to flow without interruption.